Targeting BRAF V600E in metastatic colorectal cancer: where are we today? - Motta Guerrero, R (2022)
Colorectal cancer (CRC) is the second most frequent cause of direct cancer death worldwide. The study of the molecular state of oncogenes has predictive and prognostic value in metastatic CRC (mCRC). The B-raf proto-oncogene (BRAF) gene mutation represents the 8%-12% of all mutations in mCRC. The BRAF V600E mutation, considered the most common alteration of BRAF, corresponds to a constitutive kinase with a high activating capacity of the RAS/RAF/MEK/ERK pathway after a cascade of successive phosphorylations in the transcription of genes. BRAF V600E mutation is more prevalent in women, elderly, right-sided colon cancer and Caucasian population. Unfortunately, it is considered a poor predictive and prognosis biomarker. Patients with mCRC BRAF V600E mutated (BRAFm) are generally associated with poor response to chemotherapy and short progression-free survival and overall survival. Recently, randomised clinical trials have studied the combination of different chemotherapy regimens with angiogenic inhibitors in mCRC BRAFm. In addition, new anti-BRAF and immunotherapy agents have also been studied in this population, with positive results. The objective of this review is to acknowledge the biology and molecular pathway of BRAF, critically analyse the clinical trials and the therapy options published until today and evaluate the options of treatment according to the patient's clinical presentation.